Revenue Sharing in Mining: Insights from the Philippine Case - Mendoza, Ronald U (Archīum Ateneo, 2013)
Most mining operations in developing countries are de facto public-private partnerships, as the state typically owns the resources and partners with a company or consortium in extraction. Revenue sharing is a critically important element of such partnerships, and it is the starting point for any meaningful analysis of over-all costs and benefits from mining. As a contribution to the policy discussions on this topic, this paper tries to clarify issues in properly evaluating public sector revenues from mining, using data on the Philippines as a case. The main objective here is to illustrate the main differences between macro-level and micro (firm-) level data. We find evidence that macro-level revenue sharing indicators in the Philippines fail to capture a high degree of heterogeneity in micro- (firm-) level revenue sharing outcomes. A comparison of several Philippine versus foreign mining firms in our sample indicates that there is not much difference in their average tax payments (expressed as a share of total company revenue). Furthermore, these average tax payments are actually much higher than the industry-wide average reported by the government. Clarifying and explaining these discrepancies could help determine broader net benefits from extractive industries, and thus establish whether and to what extent mining operations provide enough net gains to the country.